Exploring Students’ Motivation in Learning English at English Laboratory of UBL - Eka Sari Ayu; Yanuar Dwi Prastyo (Universitas Bung Hatta, 2023)
Motivation is essential when learning a language, even English. Without motivation, a person will lack the will or excitement to learn, which can jeopardize his academic achievement. The purpose of this study is to measure the amount of motivation of students in learning English and the prevailing motivation, whether intrinsic or extrinsic motivation. The study was carried out at the University of Bandar Lampung's language laboratory in the 2022/2023 academic year. The descriptive qualitative method was utilized by the researchers in this study. A questionnaire was utilized as the research tool, and interviews were conducted. 192 third semester students from the University of Bandar Lampung's language laboratory took part in this study. The findings of this study are that the average student has a high level of motivation based on the interpretation of the total score (4.26). The dominant student motivation in learning English is intrinsic motivation, with a total score of 4.26. In contrast, extrinsic motivation is a score of 3.94, which is defined as a moderate level of motivation. It can be concluded that students who study at the language laboratory at the University of Bandar Lampung have high motivation in learning English and are more dominant in having intrinsic motivation which means they learn English because of a desire from within themselves. REFERENCES Alizadeh, M. (2016). The impact of motivation on English language learning. International Journal of Research in English Education, 1(1), 11-15. Anjomshoa, L., & Sadighi, F. (2015). The importance of motivation in second language acquisition. International Journal on Studies in English Language and Literature (IJSEL), 3(2), 126-137. Arikunto,S. (2010). Prosedur Penelitian Suatu Pendekatan Praktik. Buku.Rineka Cipta. Jakarta. 431 hlm. Aydogan, H. (2016). Intrinsic and extrinsic motivation for English learning scale (IEM-ELS): A psycholinguistics study of reliability and validity. MCBU Sosyal Bilimber Dergisi, 14(3), 55-65. Doi: 10.18026/cursos.66920 Bogdan dan Taylor, 1975 dalam J. Moleong, Lexy. (1989). Metodologi Penelitian Kualitatif. Bandung: Remadja Karya. Brown, H. (2007). Principles of Language Learning and Teaching. 5 th edition. Addison Wesley Longman, Inc. A Pearson Education Company. Dahliana, S. (2019). Students’ motivation and responsive pedagogy in language classroom. Englisia, 6(2), 75-87. Doi 10.22373/ej. v6i2.4601 Destrini, H., Nirwana., & Sakti. I. (2018). Penerapan model pembelajaran penemuan terbimbing (Guided discovery learning) untuk meningkatkan hasil belajar dan keterampilan proses sains siswa. Jurnal Kumparan Fisika. 1(1), 13-21. Doi: 10.33369/jkf.1.1.13-21 Elliot, Andrew J; Covington, Martin, (2001) “Approach and Avoidance Motivation